Migration of Excitation Energy in Furocoumarins - Tchaikovskaya, O.N.; Dmitrieva, N.G.; Bocharnikova, E.N.; Chaidonova, V.S.; Avramov, P.V. (Frontiers in Chemistry, 2021)
The migration of excitation energy of a number of psoralen compounds has been studied. For this, the methods of induced absorption spectroscopy, stationary electron spectroscopy, fluorescence and phosphorescence, as well as quantum chemistry were used. A comparative photostability of psoralen was achieved by exposure to a XeCl excilamp irradiation (emission wavelength em = 308 nm) with parameters  = 5-10 nm, Wpeak = 18 mW/cm2, P = 8.1 J/cm3, f = 200 kHz, pulse duration 1 μs. It was found that the singlet-triplet transition played a major role in the migration of excitation energy into triplet states. Among all tested compounds, substances with an OCH3-group in the structure have the strongest effect on the spectral-luminescent characteristics.